Minimal residual disease detected by multiparameter flow cytometry is complementary to genetics for risk stratification treatment in acute myeloid leukemia with biallelic CEBPA mutations. Issue 9 (29th July 2019) - Deng, Dao-Xing; Zhu, Hong-Hu; Liu, Yan-Rong; Chang, Ying-Jun; Ruan, Guo-Rui; Jia, Jin-Song; Jiang, Hao; Jiang, Qian; Zhao, Xiao-Su; Huang, Xiao-Jun
Abstract: Acute myeloid leukemia (AML) patients with biallelic CEBPA (bi CEBPA) mutations are considered prognostically favorable, but 38–58% of them still relapse. Therefore, recognizing patients with a high risk of relapse is important. We retrospectively analyzed 83 bi CEBPA AML. Minimal residual disease (MRD) was detected by multiparameter flow cytometry (MFC). Patients with MRD positivity during consolidation chemotherapy had inferior 3-year CIR (55% vs. 36.7%; p = .037) and RFS (45% vs. 63.3%; p = .037) than those with MRD negativity. In patients with adverse cytogenetics, FLT3-ITD or MRD positivity, allogeneic hematopoietic stem cell transplantation (allo-HSCT) achieved superior 3-year CIR (0% vs. 52.8%; p = .006) and RFS (88.9% vs. 47.2%; p = .027) than did consolidation chemotherapy. Consolidation chemotherapy maintained a relatively favorable outcome (3-year CIR, 29%; 3-year RFS, 71%) in patients with intermediate cytogenetics, negative FLT3-ITD, and MRD negativity. Therefore, MFC-MRD could predict relapse and was complementary to genetics for risk stratification treatment in bi CEBPA AML.